Tantangan Pengujian Hukum Pidana Mati dan Pemidanaan Alternatif di KUHP Baru Perspektif Hak Asasi Manusia dan Integrasi Pengujian - Anggerina, Desi Puspita; Siddik, Rifqy Afrizal; Hartono, Toto; Dudikoff, Luthfy Abbad; Muidah, Ida; Candra, Firman Adi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article analyzes the challenges of judicial review of capital punishment and the integration of alternative sentencing in Indonesia's New Criminal Code (KUHP Baru), Law No. 1 of 2023, from a human rights perspective. The New KUHP reconfigures capital punishment from a primary penalty to an alternative and conditional one, allowing for probationary periods and offering various alternative sanctions such as social work and supervision. While this marks a significant reform aimed at balancing legal certainty and human rights protection, it also introduces complexities in judicial interpretation and implementation. The research questions focus on the challenges in reviewing capital punishment's constitutionality and legality, and the potential along with obstacles in integrating alternative sentencing. Utilizing a normative-juridical approach, this study evaluates the compatibility of the New KUHP's provisions with international human rights standards and explores the prospects for effective integration of alternative penalties. The findings indicate that while the alternative and conditional nature of capital punishment is a step towards humanization, its judicial review remains complex due to inherent human rights implications, particularly the right to life. Furthermore, integrating alternative sentencing requires clear guidelines and adequate infrastructure to ensure justice and rehabilitation. Recommendations include developing clear implementing regulations and enhancing judicial capacity to ensure the effective and humane application of the New KUHP.